Epigallocatechin-3-gallate (EGCG) and tricalcium silicate (C_3 S) combination as an antibacterial agent against Enterococcus faecalis - Ismiyatin, Kun; Cahyani, Febriastuti; Soetojo, Adioro; Widjiastuti, Ira; Pribadi, Nirawati; Nurkhalidah, Binar Najwa; Raftiani, Ardelia Sabrina; Pramesty, Azzahra Kinaya; Anindya, Cinitra (Universitas Airlangga, 2025)
Background: Dental caries affects 57.6% of the Indonesian population, with Enterococcus faecalis found in 80% of deep caries cases. Conventional materials used in vital pulp therapy (VPT), such as calcium hydroxide, have limitations including transient antibacterial action and poor sealing capacity. This prompts the exploration of alternative materials like epigallocatechin-3-gallate (EGCG), a polyphenol from green tea with antimicrobial activity, and tricalcium silicate (C₃S), a bioactive cement known for dentin regeneration potential. Purpose: This review evaluates the synergistic antibacterial potential of EGCG and C₃S combinations against E. faecalis, and assesses their feasibility as an alternative in VPT. Review: EGCG disrupts bacterial membranes, inhibits biofilm formation, and suppresses virulence factors, but lacks remineralization capability. Conversely, C₃S promotes dentin repair and creates an alkaline antibacterial environment, though its efficacy diminishes over time. Their combination compensates for each other’s limitations: EGCG enhances antimicrobial potency while C₃S provides long-term alkalinity and regenerative support. Conclusion: The EGCG–C₃S combination exhibits synergistic antibacterial and regenerative effects, offering a promising alternative to current VPT materials.